Ecology is the Basic Education for Landscape Architecture - Irwan, Sri Nurul Rofiqo (2014)
Landscape architecture is mentioned to be a shielding of environment, because landscape architecture is the science and art of caring for the environment. Landscape architects as the experts are always trying to minimize the environmental damage (vulnerability) and to enhance the benefits of environmental utilization process by seeking the improvement of the environmental functions, the value of beauty and the balance of environmental components of ecology. The work of landscape architecture should be a holistic ecosystem approach and taking into account the principles of ecology. Negative outcomes of development, many habitats are damaged and destroyed, damage to landscape and ecosystem, aesthetics fade, not even beautiful anymore. Many wild animals disappeared, congestion, flooding, erosion, landslides that often take casualties and material for certain areas has been difficult to obtain clean water. Vegetation in the ecosystem role is as the first manufacturer to change solar energy into potential energy for other creatures, as a source of mineral nutrients and as the biggest role to change better environment and to improve the environment quality.